CORRELATION OF BODY MEASUREMENTS AND EXERCISE WITH BLOOD PRESSURE AMONG MEDICAL STUDENTS IN LAHORE: Body Measurements and Exercise - Manzoor, Iram; Mumtaz, Aneeqa; Mushtaq, Iqra (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out correlation of body measurements and exercise with blood pressure among medical students in Lahore, Pakistan.Study Design: Correlational study.Place and Duration of Study: Akhtar Saeed Medical and Dental College, Lahore, from May to Jul 2018.Methodology: A sample of 332 students was recruited through simple random sampling technique. Resting blood pressure in sitting position along with body mass index of respondents were taken after informed consent.Results: Mean age of respondents was 21.06 ± 1.53 years. Mean sitting systolic blood pressure was 117.5 ± 8.24mm Hg, Mean sitting diastolic blood pressure was 77.9 ± 7.05mm Hg. Significant association was found between weight and both Systolic (r=1, p≤0.00) and Diastolic (r=0.01, p=0.05) blood pressure. Height was negatively correlated with systolic blood pressure (r=-0.004) and diastolic blood pressure (r=-0.07). Body mass index was also significantly associated with systolic blood pressure (r=1, p≤0.00) and diastolic blood pressures (r=0.14, p=0.00). Significant association is found between systolic blood pressure and exercise with number of days (r=-0.15, p=0.05) and diastolic blood pressure (r=-0.11, p=0.00) and duration of exercise with systolic blood pressure (r=-0.13, p=0.01) and diastolic blood pressure (r=-0.16, p=0.04).Conclusion: Weight and Body mass index are positively correlated with systolic and diastolic blood pressure.Keywords: , , , .